(3GdEbQGQ ai GdEKHGJ GdeOfi (B: s (3OQGSI ebGQfI (B/ s - (3YHOGdfGUQ UHMi GdTQjas; (3eMeO SGei YHOGdUGOb s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3Ef fXQjI GdEKHGJ ef Cge GdfXQjGJ GdbGfhfjI h CcKQgG JWHjbkG aj GdMjGI GdYedjI(B: (3ShGA eG cGf efgG aj GdeSGFd GdeOfjI Ch GdJLGQjI Ch GdLRGFjI(B: (3dCf GMJQGe bhGYO gPg GdfXQjI jMbb eUdMI GdLeGYI h GdeSGhGI Hjf GdeJbGVjf(B: (3ajKHJ GdMb GdeJfGRY ajg HeLQO EbGeI GdOdjd Ydjg(B: (3YHQ hSjdI EKHGJg GdJj ZGdHG eG Jchf TQWkG dEKHGJ GdhGbYI GdbGfhfjI GdJj CfTCJ gPG GdMb(B. (3h dbO JWhQJ COdI GdEKHGJ YHQ GdRef JWhQkG HGdZkG(B: (3aaj GdeQGMd GdChdi dhLhO GdHTQjI cGfJ hSGFdg eMOhOI JYcS MjGI GdHTQ GdHOGFjI(B: (3h CeG aj GdYUQ GdMOjK(B: (3h HeG YQaJg GdJcfhdhLjG(B: (3aJCKQJ gPg GdhSGFd h CUHM LRAkG efgG jYJeO YdjgG(B: (3h HaVd GdYde h JWhQ Gdafhf h GdGcJTGaGJ h GdGNJQGYGJ GdJj WQCJ hCOJ Edi GHJOGY GdcJGHI h GdQSe h GdJUhjQ h JSLjd GdUhJ h GdHUeGJ h aMhUGJ GdOe GdeJfhYI gGFdI GdOdGdI(B: (3JCKQJ COdI GdEKHGJ(B: (3aHYO Cf cGf GdMb jfOeL eY GdbhI h jMjG HgG Ohf eMd dGYJeGO GdCOdI h GdHjfGJ aj GdeQMdI GdJj SHbJ JCSjS GdbVGA(B: (3CUHMJ CSGdjH GdHjfGJ h JfhY WQb GdEKHGJ aj Cj OhdI ef YdGeGJ QbjgG h YXeJgG(B. (3h QZe bjGe GdMb eJi JhGaQJ CQcGfg h TQGFWg Ohf Jhba Ydi COdI EKHGJg(B: (3EdG Cf Odjd GdMb jYOd YedjkG GdMb faSg YfO EfcGQg(B: (3aGdMb YOje GdaGFOI dG jecf MeGjJg ef WQa GdSdWI GdYGeI; EPG YLR UGMHg Yf EKHGJ hLhOg(B: (3h GdbGVj dG jLO eaQkG ef Cf jbVj HGdMb def cGf HjOg GdOdjd ef Hjf GdeJOGYjf(B: (3HZV GdfXQ Ef cGf UGMHg Ce dG(B: (3h Ydjg cGf GdGgJeGe HCOdI GdEKHGJ(B: (3dCfgG GdhSjdI GdhMjOI ddhUhd Edi GdMb hGHYGO GdfGS Yf GdGOYGAGJ GdHGWdI (B{u(32013(B} (3h GdJj fXegG GdeTQY HGdbhGfjf PGJ GdUdI(B: (3aHgG jJMbb MaX GdMbhb h QO GdeXGde(B: (3h gj GdeYjGQ aj JejjR GdMb ef GdHGWd(B: (3h GdUMjM ef GdaGSO(B: (3h GdgOi ef GdVdGds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B282-300s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3eaghe GdGKHGJs; (3GOdI GdGKHGJs; (3JGQjN GdGbQGQs; (3eaghe GdGbQGQs; (3GdWHjYI GdbGfhfjI ddGbQGQs; (3GfhGY GdGbQGQs; (3NUGFU GdGbQGQs; (3GQcGf GdGbQGQs; (3MLjI GdGbQGQ aj GdGKHGJs; (3GdeHGOF GdJj JMce GdGbQGQs; (3GdSdWI GdJbOjQjI ddbGVjs; (3OhQ GdbGVj aj GdGbQGQs; (3GdGbQGQ GdbVGFjs; (3GdGbQGQ ZjQ GdbVGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs